Modification of plant‐induced responses by an insect ecosystem engineer influences the colonization behaviour of subsequent shelter‐users. (16th May 2016) - Uesugi, Akane; Morrell, Kimberly; Poelman, Erik H.; Raaijmakers, Ciska E.; Kessler, André
Summary: Herbivores that modify plant morphology, such as gall‐forming insects, can disproportionately impact arthropod community on their host plants by providing novel habitats and shelters from biotic and abiotic stresses. These ecosystem engineers could also modify plant chemical properties, but how such changes in plant quality affect the behaviour of subsequent colonizers has rarely been investigated. We explored how an initial infestation of the tall goldenrod ( Solidago altissima ) by an ecosystem engineer, the rosette gall‐midge ( Rhopalomyia solidaginis ), affects colonization behaviour of a shelter‐using beetle ( Microrhopala vittata ) through plant‐induced responses in the field. Beetles preferentially colonized plants with galls and exhibited a clumped distribution on those plants, which suggested a possible advantage for aggregating on galled plants. Accordingly, we found that beetles remained longer on galled plants with previous beetle damage than those without beetle damage. No such effect of beetle damage was found on plants without a gall. Similar interactions between galler infestation and beetle damage were found in beetle's feeding choice, leaf diterpene and serine protease inhibitor production, and volatile organic compound (VOC) emission. These plant metabolic induction and herbivore response patterns indicated that the gall‐midge can alter how plants respond to the beetle damage and that gall presence coupled with beetle damage improves leaf palatability for the beetle. Finally, we found reciprocal effects of beetles on gall‐midge performance to be neutral to slightly positive, suggesting that the observed field association of the two herbivores could be formed by plant‐mediated facilitation. Synthesis . Our study suggests that an ecosystem engineer could have significant impact on herbivore community not only by changing plant morphology, but also by altering host quality and modifying plant‐induced responses to subsequent herbivory. As such, R. solidaginis also functions as a keystone herbivore that has disproportionate effects on community dynamics and composition meditated by induced plant growth and metabolic responses. Abstract : Ecosystem engineers could have significant impact on herbivore community not only by changing plant morphology, but also by altering host quality and modifying plant‐induced responses to subsequent herbivory. As such, they may also function as a keystone herbivore that has disproportionate effects on community dynamics and composition meditated by induced plant growth and metabolic responses.